Peran Analisis Kesalahan Berbahasa Dalam Meningkatkan Kemampuan Menulis - Zubaedah Mahdiyah; Elsa Sri Lunawati; Resti Sri Monika; Aveny Septi Astriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article discusses the important role of language error analysis in improving one's writing skills. Language error analysis plays a crucial role in the language learning process, especially in the development of writing skills. By understanding the errors made in writing, one can identify frequently occurring error patterns and address them. The language error analysis method not only helps correct grammatical errors, but also opens up a deeper understanding of better language structure. With a better understanding of mistakes made, one can improve clarity, coherence, and cohesion in one's writing. This article also highlights how the use of language error analysis techniques in the learning process can provide constructive feedback to writers. Thus, this article emphasizes the importance of language error analysis in supporting the improvement of one's writing ability.